Risk management in recreation [videorecording] - Baricevic, Thomas; Moloney, Cameron; Robbio, Michael De; Video Education Australasia (Australia : Video Education Australasi, 2010)
This program addresses the nature of risk, including positive and negative consequences and emphasises the importance of personal responsibility in managing risk. An overview of how to identify, assess and reduce risks in recreational settings is provided. We meet Peta Whitford, Education Development Officer at Orienteering Victoria who walks us through the potential risks and rewards of outdoor activity
Executive producer, Simon Garner
Voice over, Shane Fankhauser
Subtitle available in English
Keywords: Risk management; Outdoor recreation -- Safety measures